Psychosocial Care: Emerging Need for the Cancer Patients in Nepal - Shah, T; Subba, S; Shah, SP (Journal of Nepal Health Research Council, 2009)
Cancer has an unsetting reminder of the stubborn grain of unpredictability, uncertainty and injustice in the human condition. It forces us to confront our lack of control over our own or others' death. The aim of this review was to acquire new knowledge on the scientific evidence based for an effect of psychosocial care on survival from cancer and well-being. The different books, journals and web sites were searched for data base information on psychological and social aspects of cancer. In the developed part of the world, there are well established psychosocial care unit, counseling services, support group concept, palliative care, home hospice, etc but in Nepal where risk for developing cancer is nevertheless. Diagnosis and treatment is being done, but no separate psychosocial unit attached to cancer hospitals. Life expectancy of cancer patients can be prolonged by early diagnosis, appropriate treatment and psychosocial services to the patients. Key words: Cancer, Emerging needs, Nepal, Psychosocial care   DOI: 10.3126/jnhrc.v7i1.2297   Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 58-61